A Simple Method for Analyzing Factor IX Activation in the Patients with Hemophilia B Variants - Yoshioka, Akira; Sakai, Toshiyuki; Yamamoto, Kazukuni; Ohkubo, Yoshiaki; Fukui, Hiromu (Thrombosis and Haemostasis, 1987)
A simple method for analyzing the activation mechanism of FIX in patients with hemophilia B variants is described. The procedure consists of rapid partial purification of FIX by BaCl2 adsorption-elution from only 3 ml of plasma, incubation with FXIa/Ca2+, SDS-PAGE, western blotting and subsequent autoradiography using monoclonal anti-FIX antibody. Abnormal FIX from the plasma of 7 unrelated patients with hemophilia BR, B+ or BM was investigated. A time course study showed that FIX in the patient with hemophilia BM (Nagoya I), BM (Nagoya II) and B Kawachinagano seemed not to be cleaved by FXIa, FIX in the patient with hemophilia B Kashihara was partially cleaved, FIX in the patient with hemophilia BM (Takatsuki) showed delayed cleavage, and that FIX in the patient with hemophilia BM (Niigata) and BM (Kiryu) was cleaved completely at a rate similar to normal FIX. These findings were identical to those previously observed for the respective factors in a purified system. The procedure used here is useful for screening for a defective activation mechanism of abnormal FIX.
Keywords: Hemophilia B; Factor IX; Activation of Factor IX; Monoclonal Antibody